Beyond Historical Narrative: Integrated Strategies for Fostering Moral Development in Sirah Nabawiyah Instruction - Addin Kholisin; Mutamakin; M Yusuf Agung Subekti (State Islamic Institute of Madura, 2025)
This article addresses the gap in Sirah Nabawiyah instruction where traditional historical transmission often fails to foster contemporary character development. This study employs a qualitative systematic literature review, analyzing major Islamic studies and education databases through thematic synthesis. Results indicate that monolithic teaching methods are insufficient for sustaining student engagement or observable moral growth. Instead, superior outcomes emerge from integrated designs that link narrative grounding with critical source work, ethical inquiry, and student-led projects. Purposeful technology use further enhances these phases by supporting active production rather than mere digitization. The synthesis emphasizes balancing collaboration with structured reflection to internalize moral vocabulary and perspective-taking. Consequently, this article proposes a teachable methodological cycle and assessment logic for character outcomes. These findings imply that curriculum planning and teacher education should prioritize replicable integrated designs and culturally sensitive dialogue to ensure Sirah learning is both historically rigorous and ethically transformative.